Physiological Responses of the Firefly Pyrocoelia analis (Coleoptera: Lampyridae) to an Environmental Residue From Chemical Pesticide Imidacloprid - Wang, Yi-zhe; Cao, Cheng-quan; Wang, Dun (Frontiers in Physiology, 2022)
Imidacloprid, a neonicotinoid insecticide, is widely applied to control the insect pests in a broad spectrum. Though the impact of residues of this chemical pesticide to non-target organisms in the field has been reported, it was not well characterized in a wide range ecosystem, especially for some species of environmental indicators living in forest. The effects of sublethal dose imidacloprid on firefly, Pyrocoelia analis, were analyzed physiologically and biochemically in this study to discuss the impact of chemical pesticide application on environmental indicators. After imidacloprid treatment, the midgut tissues of the larva of P. analis presented in abnormal morphology featured as atrophy of fat body cells, shrinking cells and destruction of midgut structure. The activities of antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) were noticeably increased during early exposure to sublethal imidacloprid and then decreased at late stage while the malondialdehyde (MDA) content significantly increased after 12 hours of exposure to imidacloprid compared with the control. Similarly, the enzyme activities of polyphenol oxidase (PPO) and acetylcholinesterase (AChE) were increased after the imidacloprid treatment and then decreased at late stage. In a summary, a sublethal dose of imidacloprid might cause destructive change of tissue structure and these damages were followed with an increasing of peroxidation that couldn’t be eliminated by antioxidant enzymes. Above results indicates that residues of imidacloprid might cause severe toxicity to non-target insects in the environment even far away from the agri-ecosystem.